Respuesta :

[tex]▪▪▪▪▪▪▪▪▪▪▪▪▪  {\huge\mathfrak{Answer}}▪▪▪▪▪▪▪▪▪▪▪▪▪▪[/tex]

let's solve for " w "

  • [tex]vw {}^{2} + y = x[/tex]

  • [tex]vw {}^{2} = x - y[/tex]

  • [tex] {w}^{2} = \dfrac{x - y}{v} [/tex]

  • [tex]w = \sqrt{ \dfrac{x - y}{v} } [/tex]

Answer:

w = √( x - y ) / v

Step-by-step explanation:

in this situation, we are actually asked to make w the subject of the formula

this !means that we should make w be equal to every other variable meaning;

w = y + x

note that this is just an example

so, let us get started

we have;

vw² + y = x

first of all we have to move the y to the right hand side

it is more like collecting like terms so that at the end of the day we only end up with w on that side

vw² = x - y

now, we have to remove the ²

we will do that by square rooting both sides

√( vw )² = √( x - y )

the square root will remove the square because they are opposites of each other.

it is more like a multiplication sign canceling a division sign or when we bring a subtraction sign to the other side of the equation and it turns to an addition sign.

in our case, it is like bringing the square to the other side of the equation and it turns to a square root sign

so,

vw = √( x- y )

we ate almost done.

it is now time to remove the v by dividing through by v

this means that we remove the multiplication sign bonding the v and w through division just like the square root removing the square

vw / v = √( x - y ) / v

w = √( x - y ) / v

therefore , our answer is

w = √( x - y ) / v